2016
DOI: 10.15184/aqy.2016.141
|View full text |Cite
|
Sign up to set email alerts
|

The eastern Asian ‘Middle Palaeolithic’ revisited: a view from Korea

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Two contrasting views are confronted. There are those who interpret early Late Pleistocene lithic technologies as reflecting the persistence of essentially Lower Paleolithic traditions (Gao, 2013;Gao & Norton, 2002;Ikawa-Smith, 1978;Li, 2014;Norton & Jin, 2009;Norton, Gao, & Feng, 2009;Seong & Bae, 2016), and those who assign them to some peculiar facies of the Middle Paleolithic (Yee, 2012;Li, 2018;Li, Li, Gao, Kuman, & Sumner, 2019;Zhang, 1985).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two contrasting views are confronted. There are those who interpret early Late Pleistocene lithic technologies as reflecting the persistence of essentially Lower Paleolithic traditions (Gao, 2013;Gao & Norton, 2002;Ikawa-Smith, 1978;Li, 2014;Norton & Jin, 2009;Norton, Gao, & Feng, 2009;Seong & Bae, 2016), and those who assign them to some peculiar facies of the Middle Paleolithic (Yee, 2012;Li, 2018;Li, Li, Gao, Kuman, & Sumner, 2019;Zhang, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that most Chinese lithic assemblages dated between 300 and 40 ka lack obvious temporal trends and are characterized by the persistence of core-and-flake technology (Gao, 2013;Gao & Norton, 2002;Ikawa-Smith, 1978;Li, 2014;Norton & Jin, 2009;Seong & Bae, 2016). Poor-quality local raw materials are preferred to exotic lithic sources, the cores show seldom preparation, their reduction most often involves direct hard hammer percussion, block-on-block technique or bipolar percussion, and retouched flakes are rare (Gao, 2013), making these industries hardly distinguishable from Chinese Lower Paleolithic traditions.…”
Section: Introductionmentioning
confidence: 99%
“…The absence of Middle Palaeolithic technologies in large areas of China is considered by some to be the consequence of relatively stable environmental conditions, absence of large-scale population replacement events, low-intensity resources exploitation, high group mobility, the production of perishable tools made of bamboo, and a preference for simple yet flexible stone tool technologies [ 38 , 68 – 73 ]. As a result, a number of researchers have argued that the term Middle Palaeolithic has no real meaning in most of East Asia [ 36 , 37 , 39 , 74 , 75 ] and should be restricted to assemblages located in peripheral areas, i.e., the Ningxia Autonomous Region [ 36 ], the Jilin Province [ 76 , 77 ], and the Inner Mongolia [ 78 ], where Middle Palaeolithic diagnostics are present in the lithic assemblages. Others use this term conventionally to designate occupations falling within the range of 300 ka to 40 ka BP, or yielding remains of archaic Homo sapiens .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, knife-shaped tools long persisted as the formal stone tool class in the Japanese lithic industries, and the "knife-shaped tool culture" is the technocomplex that is extensively distributed from Kyushu to southern Hokkaido (e.g., Ambiru 1986;Morisaki 2012;Naganuma 2010;Ono 1988;Yoshikawa 2010). In the Korean Peninsula, the Upper Paleolithic industry has tanged points (Seumbe Chireugae) from its initial stage with the emergence of blade technology (C. Bae 2017, in this issue; K. Bae 2010; Lee 2015Seong 2008Seong , 2009Seong and Bae 2016). Tanged points also appeared in Japan in the late Upper Paleolithic, around 30,000 years ago, mainly in the Kyushu region; however, they occur rather briefly, perhaps in response to small-scale human migrations from Korea or cultural transmission after the collapse of the regional environment in Kyushu, caused by the large explosive event of the Aira Volcano, which occurred some 30,000 years ago (Matsufuji 1987;Morisaki 2015).…”
Section: Paleolithic Chronologies In Japan: Short-versus Long-term Chmentioning
confidence: 99%
“…A substantial number of EUP assemblages (∼500) dated to 38,000 to 30,000 years ago further indicate that modern H. sapiens mi-grated into the Japanese Archipelago around 40,000 years ago, bringing the new lithic technological complex (Izuho and Kaifu 2015). Culture-chronological division between the Early and Late Paleolithic to characterize lithic industries in East Asia (Gao and Norton 2002;Ikawa-Smith 1978;Seong and Bae 2016) may also be validly applicable to the current Japanese Paleolithic record, although it is necessary to address the question of whether there was Paleolithic human occupation before 40 ka Figure 3. Examples of the major stone tools from the early Upper Paleolithic assemblages.…”
Section: Paleolithic Chronologies In Japan: Short-versus Long-term Chmentioning
confidence: 99%